2013
DOI: 10.1016/j.jnucmat.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Helium effects on tungsten under fusion-relevant plasma loading conditions

Abstract: Experiments were performed in the Pilot-PSI linear plasma device to study the formation of helium-induced nanostructures under high heat fluxes (>10MW.m-2), the erosion of a tungsten surface at the elevated temperatures where those structures typically form and most importantly the behaviour of a helium-induced fibreform structure during ELM-like pulses. A strong correlation between the characteristic size of the helium-induced morphology and the size of the voids observed in the near-surface region has been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
56
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 24 publications
7
56
0
3
Order By: Relevance
“…A plausible mechanism that could cause such an increased sputtering is a combination of electric field [55] and thermally-enhanced [56] sputtering, since the arc induces both a high field and a high temperature at the surface. Studies are ongoing to determine the exact yield and threshold for the ion energies reported in this paper.…”
Section: Sputtering and Secondary Electron Yieldmentioning
confidence: 99%
“…A plausible mechanism that could cause such an increased sputtering is a combination of electric field [55] and thermally-enhanced [56] sputtering, since the arc induces both a high field and a high temperature at the surface. Studies are ongoing to determine the exact yield and threshold for the ion energies reported in this paper.…”
Section: Sputtering and Secondary Electron Yieldmentioning
confidence: 99%
“…In a fully three-dimensional W lattice, the {101} planes have higher areal density and larger spacing than crystal planes in other directions. Our DFT calculation predicts that He atoms prefer to form mono-layer He clusters between {101} planes in single crystal W. The formation of He clusters or defects can be strongly dependent on He + fluence and W surface temperature3456. Due to favorable energetics, a number of He clusters can be formed between {101} planes with increasing He accumulation at elevated temperature (1400 K), resulting in He-enriched strips, as shown in Fig 5(a).…”
mentioning
confidence: 90%
“…The bombardments of W by the high-flux and low-energy He ions often lead to serious irradiation damages, such as the formation of voids, wave-like microstructures, or nanostructured fuzzes (nano-fuzzes) at the surface3456. The growth of nano-fuzzes in W is a major concern because it may cause serious etching of W surface and shorten the lifetime of the W components in ITER.…”
mentioning
confidence: 99%
“…This growth rate can be associated to an impinging He flux by considering the fraction of incoming ions that reach the bubble [20]. The slowest growth rate considered in this work corresponds to a flux of approximately 1.2 × 10 24 He m −2 s −1 , which is on the order of magnitude expected at ITER [34]. An initial bubble is created by placing eight He atoms inside a preexisting W vacancy.…”
mentioning
confidence: 99%